(untitled) (Journal of School Administration Research and Development, 2018)
We collected artifacts from 42 teachers participating in a statewide educator effectiveness system to examine the fidelity with which the formative components of the system were implemented. Specifical- ly, we collected written feedback from principals to teachers and teacher professional growth goals. We developed indicators of quality for each and examined whether there were relationships between these two indicators as well as with observations. Overall, principal feedback was often aligned with observation scores and the quality was directly related to the number of observation elements scored. Feedback is readily partitioned into two constructs: clarity of communication and instructional practices. Feedback consistently demonstrated clarity of communication but was less likely to address instructional practices. Importantly, novice teachers received poorer quality feedback than experienced teachers. Teacher Professional Growth Goals tended to be superficial and rarely included details such as specific action steps or measurable outcomes. Although exploratory, evidence that both feedback and growth goals varied to some extent by school imply that both feedback and growth goals can be impacted by better guidance.